(untitled) (Medico Legal Update, 2020)
Fly vector-borne diseases are the potential disease that can trigger an outbreak. The fly lives in a dirty place with poor sanitation, such as the market and the landfill. Some pathogens that can be transmitted by flies mechanically were bacteria such as Escherichia coli, Shigella, Salmonella, Vibrio cholera and parasites such as Balantidium coli, Entamoeba histolytica and Giardia lamblia. This study aimed to analyze the correlation between bacteria and parasite patterns on flies and the prevalence of fly vector-borne diseases. This research was conducted from May 2019 to March 2020. The flies samples were collected randomly at each research location, i.e., Tanjung Market and the Pakusari landfill. The bacteria and parasites identifications were carried out at the Microbiology and Parasitology Laboratory, Faculty of Medicine, University of Jember. The data of disease prevalence was collected in a cohort from the health centers around research locations. This study found three bacteria in market samples, 18 cases of fly vector-borne diseases and four bacteria in the landfill samples and 10 cases of fly vector-borne disease. The study indicated a significant correlation between bacteria and parasite patterns on flies with the prevalence of fly vector-borne diseases in the market, but no correlation in the landfill.